2001
DOI: 10.1080/09629350120102334
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the inhibitory effects of HA‐1077 and Y‐32885 on the translocation of PKCβI, PKCβII and PKCζ in human neutrophils

Abstract: To transmit the information inside the cell, one possibility is the action of an enzyme called kinase that phosphorylates other proteins. To study these enzymes, chemical compound synthesis was needed to know the function and the mechanism of activation. The major difficulty is creating a specific molecule for one kinase. In this study, we test the action of Rho-kinase inhibitors (HA-1077 and Y-32885) on protein kinase C (PKC) in the respiratory burst in the human polymorphonuclear neutrophils. We have shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…3) and IL‐6 promoter expression, suggesting a role of this downstream kinase in both effects. The effect on PKC in the UMR‐106 cells is consistent with a previous report showing that Rho kinase inhibition decreases PKC translocation in human polymorphonuclear neutrophils (41) …”
Section: Discussionsupporting
confidence: 91%
“…3) and IL‐6 promoter expression, suggesting a role of this downstream kinase in both effects. The effect on PKC in the UMR‐106 cells is consistent with a previous report showing that Rho kinase inhibition decreases PKC translocation in human polymorphonuclear neutrophils (41) …”
Section: Discussionsupporting
confidence: 91%
“…Additionally, almost any drug that alters Rho/ROCK will also simultaneously affect BP. An additional limitation pertains to the use of pharmacological inhibitors of the ROCK pathway as these inhibitors may have nonspecific effects through targeting of other kinases, including PKC (48). Thus, some of our effects may relate to non-ROCK effects of fasudil.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that RhoA/ROCKs/MRTF-A signaling contributes to pathological cardiac hypertrophy by promoting serum response factor (SRF)-dependent fetal gene expression. 15,17–19 Then, SRF response element reporter luciferase assays were performed in NRVMs with either decreased or increased levels of PDZ-RhoGEF. As shown in Figure S4G, Ang II-induced SRF-dependent transcription was significantly limited by PDZ-RhoGEF deficiency but was further enhanced in PDZ-RhoGEF-overexpressing NRVMs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we presume that PDZ-RhoGEF links Gα12/13-coupled GPCRs to RhoA/ ROCKs signaling upon Ang II treatment and that activated RhoA/ROCKs signaling in turn promotes PDZ-RhoGEF expression to further augment the activated signals, forming a positive feedback mechanism. However, since the use of pharmacological inhibitors of the ROCKs pathway in this study, some of the effects of fasudil on PDZ-RhoGEF expression may be related to nonspecific effects through targeting other kinases, such as protein kinase C. 10,19 Furthermore, the expression of PDZ-RhoGEF may be dynamically regulated by complex molecular networks during the progression of pathological cardiac hypertrophy. Initially, signaling pathways, including RhoA, may contribute to PDZ-RhoGEF upregulation in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 96%